Imaging the lithosphere‐asthenosphere boundary of the Indian plate using converted wave techniques. Issue 10 (3rd October 2013) - Kumar, P.; Ravi Kumar, M.; Srijayanthi, G.; Arora, Kusumita; Srinagesh, D.; Chadha, R. K.; Sen, Mrinal K.
Abstract [1] The lithospheric structure of the Indian plate has been investigated using converted wave techniques (P and S receiver functions) and a novel stacking analysis technique (without using deconvolution) applied to a large seismological data set from permanent and temporary broadband seismic stations. We observe coherent energy from at least two seismic discontinuities, i.e., the crust‐mantle (Moho) and lithosphere‐asthenosphere boundary (LAB) in the uppermost mantle. Here we provide a novel seismic image of the Indian lithosphere showing definitive evidence of its flexure, which is interpreted to be primarily caused by the hard collision at 55 Myr resulting in the world's highest mountain chain—the Himalayas and the Tibetan plateau. Results from geoidal and gravity studies do suggest postcollisional flexuring of the Indian plate; however, the flexure lacks observational constraints. The observed wavelength of the flex is 1000 km with the thickness of the Indian shield lithosphere varying from 70 km to 140 km; such a low value for a continent implies that the Indian plate has been reworked in the past. The plate deepens in the Himalayan region to a depth of 170 km. Further, the converted phases are interpreted to be resulting from the bottom of the lithosphere. We clearly demonstrate that these are distinct and different from the midlithospheric discontinuity. For a large number of stations, the midlithospheric discontinuity and LAB are clearly separated in depth. Our observations suggest that the Archaean lithosphere is no longer intact and is prone to deformation.